Fostering students’ interest in trigonometry using game-based learning strategy: a case of repeated measures - Egara, Felix Oromena; Mosia, Moeketsi (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study investigated the effectiveness of game-based learning in enhancing students’ interest in trigonometry among secondary school students in Enugu State, Nigeria. The study addressed the need for increased engagement and interest in trigonometry by leveraging successful implementations of game-based learning from other educational contexts. A true experimental design with a repeated measures approach was employed, involving senior secondary two (SS 2) students randomly assigned to either the experimental or the control group. The experimental group received trigonometry instruction through game-based learning, while the control group followed traditional teaching methods. The data collection instrument was the trigonometry interest inventory (TII) used to assess students’ interest levels at three points: pre-intervention, post-intervention, and follow-up. The repeated measures analysis of variance (ANOVA) was utilized to analyze changes in interest levels over time and between groups. The findings revealed two key findings: i) game-based learning significantly increased students’ interest in trigonometry and ii) gender, age, and location did not significantly affect the effectiveness of the game-based learning approach in fostering students’ interest in trigonometry. The study concludes that game-based learning effectively enhances students’ interest in trigonometry, offering implications for educators to improve mathematics teaching practices through interactive and engaging strategies.